ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Kinyari, Henry R; Laamena, Christina M; Ngilawajan, Darma A (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2025)
This research is a qualitative descriptive study that aims to find out the types of errors made by students in completing the story of a three-variable system of equations in class X SMA Negeri 4 Maluku Tengah. This research was conducted in class X-2 of SMA Negeri 4 Maluku Tengah for the academic year 2021/2022 from May to June 2022. The data collection techniques used were tests, interviews and documentation. The research instrument is the researcher, the test sheet about the story of the three-variable linear equation system, guidelines and interviews. Data analysis test results to find out the types of errors in accordance with the procedure New people include comprehension error, transformation errors, process skills and encoding errors. The selection of subjects to be interviewed was 3 students, including 1 student with high ability, 1 student with moderate ability and 1 student with low ability. Of the three, based on the results of the interview, it was found that those with high abilities only made mistakes on question number 1, where the indicators of understanding errors and writing the final explanation were, while subjects with medium and low abilities made errors indicators on each question. The main thing that causes the emergence of some differences, because the ability of different subjects so that the ability to analyze is also different